Poverty Among Single Elderly Women Under Different Systems of Old-Age Security: A Comparative Review - Jürg K. Siegenthaler (Luxembourg Income Study (LIS), 1996)
Comparisons of the economic position of single older women in various industrialized countries have shown substantial differences, especially regarding the proportion of widows, divorcees, and never-married women experiencing poverty. This review aims at a comparative assessment of existing studies that have examined these differences, focusing on six nations: France, Germany, the Netherlands, Sweden, Switzerland, and the United States. The review also encompasses relevant comparative benefit studies and probes into the institutional arrangements of old-age security schemes in each country that may explain higher or lower poverty rates for women aged 65 or over who are on their own.
Keywords: 330; Altersvorsorge; Armut; Alleinerziehende; Frauen; OECD-Staaten